ANALISIS KOMPETENSI SOSIAL GURU BERDASARKAN SERTIFIKAT PENDIDIK - Islami, Anisya; Hermita, Neni; Alim, Jesi Alexander (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2022)
The research aims to know teachers’ social competences based on the educator certificate. The research method used in this study is a descriptive quantitative method. The data-collection technique used was a questionnaire technique. The data analysis technique used is a descriptive analysis. Teachers’ social competences based on educator certificates in general have a good category. This corresponds with teachers’ social competence indicators of being inclusive and objective, adapting to the assigned environment, effective communication and good manners in communication.